Value addition and product diversification of mango ginger (Curcuma amada) - Sharma, Dhanmaya; Upadhyay, Sujata (Journal of Postharvest Technology, 2024)
Curcuma amada (mango ginger) is a plant of the ginger family Zingiberaceae and is closely related to turmeric. The rhizomes are very similar to ginger but have a raw mango taste. The Curcuma plant has powerful properties i.e. an antibacterial, antifungal, anti-inflammatory and an antioxidant, good appetizer, calming agent, relieves pain, anti-allergenic, analgesic, works as a depressant, cytoxic. The study was undertaken at Dept. of Horticulture, Sikkim University, Gangtok during 2015-2017 with the objectives to prepare various processed products of mango ginger for value addition, to analyze the nutritional content in fresh rhizomes and processed products and to assess the acceptability of processed products by the consumer. Products (pickle, candy, nectar and powder) were prepared and examined on its quality, texture, taste, aroma and firmness through organoleptic test undergone by the people of various aged group. In pickle 8 treatment combinations were taken with three replications. In nectar and candy, four treatments were taken with four replications. In mango ginger powder, 6 treatments were taken with three replications. The estimation was done for both fresh and processed products, like TSS, Vitamin C, Fibre estimation, acidity (citric and acetic acid), nutrient analysis of processed products through Inductively coupled plasma mass spectrometry (ICP-MS) and Curcumin analysis by UV spectrophotometry. Essential oil extraction, titrable acidity, T.S.S., Vitamin C and Fibre estimation were done. The statistical analysis was done using Completely Randomized Block Design. Among all the treatments, pickle, treatment T3 (which was prepared with 10% salt concentration, oil + spices) and T7 (15% salt, oil + spices) prepared were found to be best and most preferred by the consumer. For candy treatment T3 (85% sugar + 0.03% citric acid) and T2 (75% sugar + 0.03% citric acid) were found to be the best and for nectar treatment T3 ( 25% sugar) was found best as per organoleptic test conducted. The curcumin content in the powder was found highest in the treatment T4 (700C +2days). In the mango ginger rhizome content good amount of ascorbic acid in raw form was observed and after processing significant loss was not observed. Majority of major and minor elements were observed in mango ginger (raw) and its processed products.